Fetal hyperechoic kidney cohort study and a meta-analysis - Yang, Wei; Zu, Shujing; Jin, Qiu; Liu, Yu; Wang, Chao; Shen, Huimin; Wang, Ruijing; Zhang, Hui; Liu, Meimei (Frontiers in Genetics, 2023)
Objective ： To investigate the positive rate of chromosomal and monogenic etiologies and pregnancy outcomes in fetuses with hyperechoic kidney, and to provide more information for genetic counseling and prognosis evaluation. Methods: We performed a retrospective analysis of 25 cases of hyperechoic kidney diagnosed prenatal in the Second Affiliated Hospital of Harbin Medical University and Harbin Red Cross Central Hospital (January 2017 to December 2022). Furthermore, we conducted a meta-analysis of a series of hyperechoic kidneys (HEK) in the literature to assess the incidence of chromosomal and monogenic etiologies, mortality, and pooled odds ratio (OR) estimates of the association between the incidence of these outcomes and other associated ultrasound abnormalities. Results: 25 fetuses of HEK were enrolled in the cohort study, including 14 with isolated hyperechoic kidney (IHK) and 11 with non-isolated hyperechoic kidney (NIHK). Chromosomal aneuploidies were detected in 4 of 20 patients (20%). The detection rate of pathogenic or suspected pathogenic copy number variations (CNVs) was 29% (4/14) for IHK and 37% (4/11) for NIHK. Whole exome sequencing (WES) was performed in 5 fetuses, and pathogenic genes were detected in all of them. The rate of termination of pregnancy was 56% in HEK. 21 studies including 1178 fetuses were included in the meta-analysis. No case of abnormal chromosome karyotype or ( intrauterine death ) IUD was reported in fetuses with IHK. In contrast, Tthe positive rate of karyotype in NIHK was 22% and that in HEK was 20%, with the ORs of 0.28 (95%CI 0.16-0.51) and 0.25, (95%CI 0.14-0.44), respectively. The positive rate of (chromosome microarray analysis) CMA in IHK and NIHK was 59% and that in NIHK was 32%, with the ORs of 1.46 (95%CI 1.33-1.62) and 0.48(95%CI,0.28 -0.85), respectively. The positive rate of monogenic etiologies in IHK was 31%, with the OR of 0.80 (95%CI 0.25-2.63). In IHK, Tthe termination rate was 21% and neonatal mortality was 13%, in IHK and NIHK with the ORs of 0.26